Decellularized spinal cord meninges extracellular matrix hydrogel that supports neurogenic differentiation and vascular structure formation. (7th September 2021) - Ozudogru, Eren; Isik, Melis; Eylem, Cemil Can; Nemutlu, Emirhan; Arslan, Yavuz Emre; Derkus, Burak
Abstract: Decellularization of extracellular matrices offers an alternative source of regenerative biomaterials that preserve biochemical structure and matrix components of native tissues. In this study, decellularized bovine spinal cord meninges (dSCM)‐derived extracellular matrix hydrogel (MeninGEL) is fabricated by employing a protocol that involves physical, chemical, and enzymatic processing of spinal meninges tissue and preserves the biochemical structure of meninges. The success of decellularization is characterized by measuring the contents of residual DNA, glycosaminoglycans, and hydroxyproline, while a proteomics analysis is applied to reveal the composition of MeninGEL. Frequency and temperature sweep rheometry show that dSCM forms self‐supporting hydrogel at physiological temperature. The MeninGEL possesses excellent cytocompatibility. Moreover, it is evidenced with immuno/histochemistry and gene expression studies that the hydrogel induces growth‐factor free differentiation of human mesenchymal stem cells into neural‐lineage cells. Furthermore, MeninGEL instructs human umbilical vein endothelial cells to form vascular branching. With its innate bioactivity and low batch‐to‐batch variation property, the MeninGEL has the potential to be an off‐the‐shelf product in nerve tissue regeneration and restoration.